A model of structural equations of possible factors that cause poor academic performance in mathematics (2020)
This research examined through a model of structural equations, the possible factors of the Affective Domain that favor students under academic performance in Mathematics. The sample was 380 students between 4th and 7th grades of Basic Education from two public institutions. The instrument included sociodemographic, academic, pedagogical, and basic descriptors of the affective domain of mathematics. The results highlight that students' likings, attitudes and beliefs in mathematics, together with the activities that the teacher implements in the classroom, are decisive in the academic performance of the students.